2020
DOI: 10.1177/1532673x20906459
|View full text |Cite
|
Sign up to set email alerts
|

Mentoring the Next Generation of Women Candidates: A Field Experiment of State Legislators

Abstract: This experiment sent state legislators an email from an individual seeking advice on running for office, varying the gender and party of the sender. This project explores two inquiries—who the legislators choose to respond to and how the legislators’ own gender and partisan identities shape that decision. I theorize that women in politics is a salient issue for legislators; therefore, they will be more willing to advise politically ambitious women. Overall, I find that legislators are more willing to offer hel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…2 Requests for career mentorship have found null results (Kalla, Rosenbluth and Teele 2017;Thomsen and Sanders 2020) or pro-woman bias (Rhinehart 2020) in the USA, null results in New Zealand (Golder, Crabtree and Dhima 2019) and pro-women bias in Canada (Dhima 2020). Requests for personal help to access services have generated null results in Canada (Loewen and MacKenzie 2019;Dhima 2020) and Latin America (Magni and Ponce de Leon 2020), and pro-woman bias in Europe (Magni and Ponce de Leon 2020).…”
Section: Bias In Politician Responsivenessmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Requests for career mentorship have found null results (Kalla, Rosenbluth and Teele 2017;Thomsen and Sanders 2020) or pro-woman bias (Rhinehart 2020) in the USA, null results in New Zealand (Golder, Crabtree and Dhima 2019) and pro-women bias in Canada (Dhima 2020). Requests for personal help to access services have generated null results in Canada (Loewen and MacKenzie 2019;Dhima 2020) and Latin America (Magni and Ponce de Leon 2020), and pro-woman bias in Europe (Magni and Ponce de Leon 2020).…”
Section: Bias In Politician Responsivenessmentioning
confidence: 99%
“…Given these competing forces and contextual diversity, the experimental literature on gender bias in politician responsiveness to constituent requests has been unsurprisingly mixed. 5 For example, politicians' responsiveness to requests for mentorship (informal personal assistance) in New Zealand exhibits no bias (Golder, Crabtree and Dhima 2019), while US studies find no gender bias (Kalla, Rosenbluth and Teele 2017) or pro-woman bias (Rhinehart 2020), and a Canadian study shows a pro-woman bias, especially among female politicians (Dhima 2020). Responsiveness to requests for personal help accessing government services show no gender bias in Canada (Loewen and MacKenzie 2019) or in the 4 Indeed, Wiener (Forthcoming) finds that while female politicians are more responsive at baseline to a meeting request from a women's anti-sex trafficking organization, male politicians increase their responsiveness to close that gap when accountability incentives-voter mobilization or informational assistance are mentioned.…”
Section: Bias In Politician Responsivenessmentioning
confidence: 99%
“…This could be problematic if differences in perceived gender influence reply rates. Audits have failed to find evidence of gender discrimination in constituency service (Butler 2014; Golder, Crabtree, and Dhima 2019; Rhinehart 2020; Thomsen and Sanders 2019). Nonetheless in future audits I recommend using names with equally gendered perceptions.…”
Section: Name Perceptionsmentioning
confidence: 99%
“…Two studies found no bias in elected officials' responses to young men and women seeking political advice in the USA (Kalla, Rosenbluth, and Teele 2017) and New Zealand (Golder, Crabtree, and Dhima 2019). Two other studiesconducted in Canada and the USAactually found that elected officials respond more to women than men interested in running for office (Dhima 2018;Rhinehart 2020). Another study found no discrimination from bureaucrats toward men and women inquiring about public housing (Einstein and Glick 2017).…”
mentioning
confidence: 99%
“…1 Work on gender bias is more limited. The few studies available have examined elected officials' responsiveness to young men and women seeking political mentorship and found no bias (Golder, Crabtree, and Dhima 2019;Kalla, Rosenbluth, and Teele 2017) or a positive bias toward women (Dhima 2018;Rhinehart 2020). Another study assessed how officials' gender influenced citizens' engagement with their representatives (Costa and Schaffner 2018).…”
mentioning
confidence: 99%